ANALISIS PERAN KOPERASI DALAM MENINGKATKAN USAHA MIKRO DI DESA BUKIT HARAPAN KECAMATAN MERLUNG - Silvia roza; Erwin saputra siregar; Laily ifazah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research is based on the role of cooperatives in increasing micro-enterprises in Bukit Harapan village, Merlung District. The purpose of this study is to determine the role of cooperatives in developing micro businesses in Bukit Harapan village, Merlung sub-district and to determine the role of cooperatives in empowering the community's economy, especially micro entrepreneurs in terms of income. The type of research method used is qualitative research. The results of this study show that cooperatives have a very important role in developing micro businesses in Bukit Harapan Village, as evidenced by the results of research to 15 resource persons. All micro business actors agreed that cooperatives are very helpful for them in opening and developing their businesses. In addition to cooperatives playing a role in developing micro businesses, cooperatives also play a role in growing the community's economy so that people's income increases. This is in line with the findings of research to 15 interviewees who said that, after they increased capital for the business they had, their income also increased.